Fifty key writers on photography - Durden, Mark. (Routledge key guides, 2013)
"Fifty Key Writers on Photography is a clear and concise survey of some of the most significant writers on photography who have played a major part in defining and influencing our understanding of the medium. It provides a succinct overview of writing on photography from a diverse range of disciplines and perspectives and examines the shifting perception of the medium over the course of its 170 year history. Key writers discussed include:Roland BarthesCharles Baudelaire Christian MetzHenri Cartier-BressonGeoffrey BatchenFully cross-referenced and in an A-Z format, this is an accessible and engaging introductory guide"--